Cannabis induced psychosis: A systematic review on the role of genetic polymorphisms. (July 2022) - Carvalho, Cláudia; Vieira-Coelho, Maria A.
Abstract: Objective: Cannabis sativa is a recreational drug commonly consumed in Europe and is getting popularity for both recreational and therapeutic use. In some individuals, the use of cannabis leads to psychotic disorders. This systematic review summarizes the current evidence linking genetic polymorphisms and inter-individual susceptibility to psychosis induced by cannabis. Method: Studies published from 2005 to 2020 were identified through Medline using PubMed, Web of Science and Scopus database and searches were conducted according to PRISMA guidelines. Initial search was performed with terms: "cannabis induced psychosis" AND "genetics". Results: From the initial group of 108 papers, 18 studies met our inclusion criteria. Many of the findings revealed associations with genetic polymorphisms modulations of genes involved directly (COMT, DRD2 and DAT) or indirectly (AKT1) to dopamine pathways. The most consistent finding was with COMT rs4680, where the presence of the Val allele was associated with a higher risk for cannabis-induced psychosis. This higher susceptibility was also reported for AKT1 (rs2494732) with the CC genotype. Of note, the only genome-wide association study identified a significant signal close to the cholinergic receptor muscarinic 3 represented by rs115455482 and rs74722579 predisposing to cannabis-induced hallucinations and remarkably no dopaminergic target was found. Conclusion: Actual evidence supports the role of dopamine in cannabis induced psychosis. However, most of genetic polymorphism studies have as a starting point the pre-existing dopaminergic theoretical basis for psychosis. This alerts to the importance of more broad genetic studies. Integrate genetic results into biological systems may enhance our knowledge of cannabis induced psychosis and could help in the prevention and treatment of these patients. Graphical Abstract: ga1 Highlights: Considering risk for cannabis induced psychosis, most consistent genetic associations described are related with dopaminergic pathways. COMT and AKT1 are the two most studied genes. Studies evaluating the genetic influence on cannabis-induced psychosis in healthy individuals are still scarce. Great heterogeneity in the definition of phenotypes and endophenotypes. The variety of measuring instruments and experimental design makes it difficult to pull together all studies in a suitable systematic review.